Environmental Literacy Analysis of Junior High School Students in Pekanbaru - Wulan Indri Safitri; Evi Suryawati; Yustina Yustina (Journal of Educational Sciences, 2020)
This study aims to determine the environmental literacy profile of junior high school students in Pekanbaru, Indonesia. This study used a survey method with sampling technique by cluster random sampling. The survey was conducted by performing a Test Question and a Middle School Environment Literacy Survey (MSELS) to 372 students. The parameters of this study consisted of  ecological knowledge, cognitive skills, attitudes and behavior. The data analysis technique was in the form of descriptive analysis using the average score of achievement of each parameter. The results of this study indicate that the environmental literacy of junior high school students in the  Pekanbaru obtained an average value of 61 (with range of 100). The achievement of environmental literacy parameters for ecological knowledge, cognitive skills, attitudes and behaviors amounted to 48, 29, 73 and 71, respectively. Environmental literacy of junior high school students in Pekanbaru is included in the medium category where knowledge and attitudes contribute to environmental literacy.